Digital Divide on Financial Development in Asia-Pacific Region: The Role of Contextual Factors - Bao Trung Phan; Dao Le-Van; Dinh Van Nguyen; Thi Kim Duyen Nguyen (Scientific Annals of Economics and Business, 2025)
This study delves into the influence of the digital divide on financial development, considering contextual factors, particularly institutional frameworks. The Asia-Pacific region, chosen for its diverse variables across countries, was pivotal in elucidating this relationship. This research reveals that the impact of the digital divide on financial development becomes evident about two years post-implementation by addressing time lag and endogeneity concerns with instrumental variables. Notably, the study highlights how the digital divide affects financial inclusion advancements, with institutional quality moderating the strength of this relationship but not altering its trajectory. Monopoly is recognized as a constraint on financial development, supporting previous research. Policymakers in transitioning economies should heed the delayed effects of digital transformation, emphasizing long-term strategies considering multifaceted impacts on financial development.